Fundamental Cell Morphologies Examined With Cryo-TEM of the Species in the Novel Five Genera Robustly Correlate With New Classification in Family Mycobacteriaceae - Yamada, Hiroyuki; Chikamatsu, Kinuyo; Aono, Akio; Murata, Kazuyoshi; Miyazaki, Naoyuki; Kayama, Yoko; Bhatt, Apoorva; Fujiwara, Nagatoshi; Maeda, Shinji; Mitarai, Satoshi (Frontiers in Microbiology, 2020)
A recent study proposed the novel classification of the family Mycobacteriaceae based on genome analysis of core proteins in 150 basonym Mycobacterium species and the results from these analyses supported the existence of five distinct monophyletic groups within the genus basonym Mycobacterium. That is, basonym Mycobacterium has been divided into two novel genera for rapid grower Mycobacteroides and Mycolicibacterium, and into three genera for slow grower Mycolicibacter, Mycolicibacillus, and an emended genus Mycobacterium, which includes all the major human pathogens. Here, cryo-TEM examinations of 1816 cells of 31 species (34 strains) belonging to the five novel genera were performed. The fundamental morphological properties of every single cell, such as cell diameter, cell length, cell perimeter, cell circularity, and aspect ratio were measured and compared between these genera. In 50 comparisons on the five parameters between any two genera, only four comparisons showed “non-significant” differences. That is, there are non-significant differences between slow grower genus Mycolicibacillus and genus Mycobacterium in cell diameter (p = 0.15), between rapid grower genus Mycobacteroides and slow grower genus Mycobacterium in average cell length (p > 0.24), between genus Mycobacteroides and genus Mycobacterium (p > 0.68) and between genus Mycolicibacter and genus Mycolicibacillus (p > 0.11) in average cell perimeter, and between genus Mycolicibacterium and genus Mycobacterium in circularity (p > 0.73). The other 45 comparisons showed significant differences between genera. Genus Mycobacteroides showed the longest average cell diameter, whereas genus Mycolicibacter showed the shortest average diameter. Genus Mycolicibacterium showed the most extended average cell length, perimeter, and aspect ratio, whereas genus Mycolicibacillus showed the shortest average cell length, perimeter, and aspect ratio. Genus Mycolicibacillus showed the highest average cell circularity, whereas genus Mycobacterium showed the lowest average cell circularity. These fundamental morphological data strongly support the recent new classification in family Mycobacteriaceae, and this classification is rational and effective in the study of the members of family Mycobacteriaceae. Because both genus Mycolicibacterium and genus Mycobacterium contains many species and showed larger significant standard deviations in every parameter, these genera may be divided into novel genera which show common genotype and phenotypes in morphology and pathogenicity.